PENGUKURAN KADAR ALKOHOL BERBASIS ARDUINO PADA PROSES FERMENTASI MENGGUNAKAN SENSOR TEKANAN DAN TEMPERATUR - ISWANTI SIHALOHO (LP2MTBM MAKARIOZ, 2022)
Technological developments in the field of microcontrollers make it possible to build a monitoring system that can be used bythe wider community in making and producing food products from fermentation with better quality and taste. Economical,portable, and remote sensing systems were needed in the 20th century. In this study, an alcohol content monitoring systemwas built using the Arduino Uno microcontroller, pressure sensor and BMP-280 temperature sensor to display pressure andtemperature during the fermentation process. The system is used to look at the relationship between pressure and CO2levels, as well as the concentration of alcohol produced during fermentation. The gas pressure detected by the BMP-280sensor is displayed in graph form on a labview program that is already connected to the arduino beardboard and alcoholcontent is obtained through calculations. The fermentation sample used there are 4 samples, namely by varying sugar 5grams and 10 grams and variations of yeast that is 1 gram and 2 grams. Monitoring is carried out until the gas pressureproduced is constant. The results showed that the gas pressure differed in each sample and the gas pressure tended toincrease and would be constant at the 64th, 180th, 120th, and 437th minutes in each sample, and the percentage of alcoholproduced was 0.005%, 0.00004%, 0.007%, 0.0154%.